Textbook of female sexual function and dysfunction : diagnosis and treatment - Goldstein, Sue W.; Kim, Noel N.; Clayton, Anita H.; Goldstein, Andrew, M.D.; Kingsberg, Sheryl A. (Hoboken, NJ : Wiley, 2018)
A comprehensive text on female sexual function and dysfunction that offers a multi-disciplinary, biopsychosocial approach to diagnosis and treatment Textbook of Female Sexual Function and Dysfunction offers a multi-disciplinary, biopsychosocial approach and provides guidance for the safe and effective diagnosis and treatment of various sexual health issues. With contributions from an international panel of experts, the text provides the scientific basis of the clinical recommendations for dealing with problems of sexual, desire, arousal, orgasm and pain. The text is clearly organised around the four major disease states in female sexual dysfunction (FSD) and is officially endorsed by the International Society for the Study of Women's Sexual Health (ISSWSH). The authors cover a wealth of topics such as hypoactive sexual desire disorder, psychological management of sexual disorders, anatomy and physiology of sexual dysfunction and pain and information on future developments and research. In addition, the text reviews all FDA approved medications for sexual dysfunction and contains consideration of off-label treatments for FSDs. This important text: -''' Offers the only textbook to highlight female sexual dysfunction in light of recently approved FDA medications -''' Contains a unique biopsychosocial approach from a collaborative team of physicians, psychologists, physical therapists as well as other sexual health professionals -''' Presents a comprehensive text led by one of the foremost global experts in Women's Sexual Health, Irwin Goldstein, founder of ISSWSH, with three other past presidents and one president-elect Written for any professional dealing with women's sexual health, Textbook of Female Sexual Function and Dysfunction offers an invaluable guide to the most safe and effective diagnosis and treatment.
History of the international society for the study of women's sexual health / Sue W. Goldstein -- Sexual medicine education and training / Sharon J. Parish and Johannes Bitzer -- Nosology and epidemiology of hypoactive sexual desire disorder / Leonard R. Derogatis -- Central nervous system anatomy and neurochemistry of sexual desire / James G. Pfaus and Sherri L. Jones -- Psychological management of hypoactive sexual desire disorder / Sheryl A. Kingsberg and Stanley Althof -- Pathophysiology and medical management of hypoactive sexual desire disorder / Anita H. Clayton and Linda Vignozzi -- Nosology and epidemiology of arousal disorders in women / Leonard R. Derogatis -- Anatomy and physiology of arousal / Kwangsung Park and Noel N. Kim -- Psychological management of arousal disorders / Isbelia Segnini and Tuuli M. Kukkonen -- Pathophysiology and medical management of female genital arousal disorder / Irwin Goldstein -- Pathophysiology and medical management of persistent genital arousal disorder / Barry R. Komisaruk and Irwin Goldstein -- Nosology and epidemiology of female orgasm disorder / Leonard R. Derogatis -- Peripheral and central neural bases of orgasm / Emmanuele A. Jannini, Nan Wise, Eleni Frangos, Barry R. Komisaruk -- Psychological management of orgasm disorders / Sara Nasserzadeh -- Musculoskeletal management of female orgasm disorder / Karen Brandon -- Pathophysiology and medical management of female orgasm disorder / Irwin Goldstein and Barry Komisaruk -- Pathophysiology and medical management of female orgasmic illness syndrome / Irwin Goldstein and Barry R. Komisaruk -- Nosology and epidemiology of dyspareunia and vulvodynia / Tami S. Rowen and Andrew T. Goldstein -- Anatomy and physiology of sexual pain / Melissa A. Farmer -- Psychological management of provoked vestibulodynia / Caroline F. Pukall and Sophie Bergeron -- Musculoskeletal management of pelvic and sexual pain disorders / Sara K. Sauder, Fiona McMahon, and Amy Stein -- Medical management of dyspareunia and vulvovaginal pain / Andrew T. Goldstein and Susan Kellogg Spadt -- Future developments and research / James A. Simon.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Keywords: Sexual disorders -- Diagnosis; Sexual disorders -- Treatment; Women -- Sexual behavior; Sexual Dysfunction, Physiological; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Sexual disorders -- Treatment; Women -- Sexual behavior; Sexual Dysfunction, Physiological -- diagnosis; Sexual Dysfunction, Physiological -- therapy; Women; Sexuality -- physiology; Electronic books